The Validity and Practicality of the Chemistry Learning Device by Using STEM-PjBL Model - Suwadarma, K W; Sudiatmika, A A I A R; Suja, I W (Universitas Pendidikan Ganesha, 2020)
The purpose of this research was to produce the valid and practical learning device using STEM-PJBL to be applied in the chemistry class of Senior High School. The Research was conducted based on the steps of development research according to Borg and Gall. The students of the research included lesson plan, student worksheet, teaching material and evaluation instrument; while the objects of the research were validity and practically of the learning devices themselves. The research was conducted at SMA Negeri 1 Kuta Selatan in March to April 2019, by envolving the XI grade science students as the research population. The data retrieval used validity sheet that was taken by the expert, readability test sheet by teachers and students and students response questionaire about the learning process. The result of the research showed the content of lesson plan as 1, student worksheet as 0,875; material text as 0,80 and evaluation instrument as 0,97; so that all were categorized as valid. The practically score based on the readability of lesson plan as 3,78; student worksheet as 3,68; material text as 3,83; and evaluation instrument as 3,64 ; all were categorized very practical. The practically score of learning device based on the sudents response during the learning process on initial field test was as 4,59 (very practical) and on the main field test was 4,24 (very practical). Therefore, the STEM-PJBL produced in this reseach was categorized in very valid and very practical.Keywords: Learning devices, STEM-PJBL Model, Chemistry, validity and practicality